KINERJA RELAWAN DEMOKRASI (RELASI) DALAM SOSIALISASI PEMILIHAN UMUM SERENTAK 2019 DI KABUPATEN KAMPAR - Anita, Rimta; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by the formation of volunteer democracy in Kampar District to improve the quality of the electoral process, increase voter participation, increase public confidence in the democratic process and generate civil society volunteerism in the electoral and democratization agenda. However, in the process of direct socialization to the public, various problems were still found, both internal and external. The existing problems make the duties and functions of democracy volunteers less felt by the community as targets of socialization. This study aims to determine the Performance of Democratic Volunteers (Relation) in the Socialization of the 2019 Concurrent General Election in Kampar Regency and to find out the obstacles faced by Democratic Volunteers (Relation) in the Socialization of the 2019 Simultaneous General Election in Kampar Regency. The method used in this research is qualitative with a descriptive approach. The types of data in this study are primary data and secondary data. Data collection techniques in this study were interviews and documentation. The data analysis technique used is descriptive qualitative.                The results of this study indicate that the Performance of Democratic Volunteers (Relationships) in the Socialization of the 2019 Concurrent General Election in Kampar Regency can be assessed from several performance indicators, namely: (1) Quality (2) Quantity (3) Timeliness (Timeliness) ) (4) Effectiveness Cost (5) Need For Supervision (Need for Supervision) (6) Interpersonal Impact (Relationships between individuals). As for the Obstacles faced by Democratic Volunteers (Relation) in the Socialization of the 2019 Concurrent General Election in Kampar Regency, namely the Duties of Democracy Volunteers (Relationships) are less clear, Democratic Volunteers (Relation) lack experience, budget constraints, limited number of personnel or personnel, limited time due to regional coverage Broad and Lack of Community Response in Socialization. The conclusion of this study shows that the Performance of Democratic Volunteers (Relationships) in the Socialization of the 2019 Concurrent General Election in Kampar Regency is still not optimal. This is also caused by several obstacles experienced by the Volunteer Democracy (Relation) during the socialization. Keywords: Democracy Volunteer Performance